Association of HLA (Class I & II) and Susceptibility to Hydatid Cyst Disease - Al-Joofy, Ikbal Kh.; Mahmoud, Mohanad H.; Maki, Amal M.; Omar, Amera J.; Shareef, Salwa M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Hydatid cyst disease is a parasitic zoonotic disease caused by genus Echinococcus. This disease believed to has genetic background in it's aetiopathogenesis course .The aim of this study is to shed light on the possible correlation between HLA-class I (A,B,C) & HLA-class II (DR & DQ) antigens and the susceptibility to this disease.Patients & Methods: Fifty patient with hydatid cyst disease before undergoing surgical operation were investigated for HLA. Class I and class II by using microlymphocytotoxicity test. The results were compared with 115 healthy control.Results: Significant increased trend of HLA-A28 and A-11, -B18 and B-35, -DR3 and DR-11 (P